Morphometric Analysis and Condition Factor of Freshwater Prawn, Macrobrachium lamarrei (Crustacea-Decapoda) from the Gomti River, Lucknow, Uttar Pradesh, India - Lodhi, Samiksha; Ahmed, Aman; Swami, Veena P.; Shukla, Sanjive (UTTAR PRADESH JOURNAL OF ZOOLOGY, 2024)
The present investigations on morphometric analysis and condition factor of freshwater prawn, Macrobrachium lamarrei (in both sexes) from The Gomti river, Lucknow, Uttar Pradesh, India. The freshwater prawn, locally known as “Jhinga” was the subject of this study. Prawn samples had been collected in different months of both sexes, and a close relation between their length and weight were observed. The morphometric analysis showed that females ranged from 31-57 mm in length, with their weight ranges from 0.31-1.39g, which are larger than the males (21- 36mm) with their higher weight range (0.13- 0.49g). A high correlation coefficient was observed in males (R2 = 0.808) and females (R2 = 0.881) separately. There were significant differences in the condition factors of males and females at P = .05. The lowest condition factor (CF) value for the males was observed in January (CF= 1.06) and highest in September (CF= 1.52), while in the females CF was the highest value in January (CF=0.82) and the lowest one in March (CF=0.75). The sex ratio of male: female (1.0: 2.10) was found, indicating that females are significantly greater in number than males.